PARADIGMA ILMU INTEGRATIF PERSPEKTIF KUNTOWIJOYO - Sriyono, Sriyono; Andhim, Muk; Ridwan, Mohammad (Program Studi Pendidikan Agama Islam Tarbiyah IAI Muhammadiyah Bima, 2024)
The dichotomy between religion and science is one of the causes of the decline of Muslims. Kuntowijoyo offers an integrative scientific paradigm as a solution. This article examines Kuntowijoyo's thoughts from various primary and secondary literature with the aim of exploring the concept of an integrated scientific paradigm initiated by Kuntowijoyo. This type of research is library research with a qualitative approach. The data collection method is using documentation. The data analysis methods include reduction, data presentation and drawing conclusions. The results of this research reveal the concept of Kuntowijoyo's integrative science paradigm in the structure of the philosophy of science. The ontology is theo-anthropocentric monotheism, the epistemologies are integralization and objectification and the axiology is rahmatan lil-'alamin. Dikotomi antara agama dan sains menjadi salah satu sebab kemunduran umat Islam. Kuntowijoyo menawarkan sebuah paradigma keilmuan integratif sebagai solusinya. Artikel ini mengkaji pemikiran Kuntowijoyo dari berbagai literatur primer dan sekunder dengan tujuan menelusuri konsep paradigma keilmuan terpadu yang digagas Kuntowijoyo. Jenis penelitian ini adalah penelitian kepustakaan dengan pendekatan kualitatif. Metode pengumpulan data menggunakan dokumentasi. Adapun metode analisis data berupa reduksi, penyajian data dan penarikan simpulan. Hasil dari penelitian ini mengungkap konsep paradigma ilmu integratif Kuntowijoyo dalam struktur filsafat ilmu. Ontologinya berupa tauhid teo-antroposentris, epistemologi berupa integralisasi dan objektivikasinya serta aksiologinya berupa rahmatan lil-‘alamin.